Physiological and Pharmacological Regulation of Hepatic 3-Hydroxy-3- Methylglutaryl Coenzyme A Reductase - Ness, Gene C. (Current Medicinal Chemistry - Immunology, Endocrine & Metabolic Agents, 2003)
The conversion of 3-hydroxy-3-methylglutaryl coenzyme A to mevalonate, catalyzed by 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMGR), is considered to be the ratelimiting step in the overall pathway of cholesterol biosynthesis. Although expressed in virtually every tissue, HMGR is normally expressed at the highest level in liver. Also the magnitude of regulation of HMGR in liver exceeds that in any other tissue. Thus, this review focuses on regulation of hepatic HMGR. Feedback regulation by the end product of the pathway, cholesterol, has been, perhaps, the most extensively studied of the physiological and pharmacological factors that act to regulate HMGR expression. This constitutes an important homeostatic mechanism to maintain cholesterol levels within rather narrow limits. A series of recent studies have now demonstrated that this regulation occurs at the level of mRNA translation - not at the level of transcription as has been widely accepted. The rapid stimulation of hepatic HMGR activity by insulin is due to increased transcription rather than a change in phosphorylation status. Glucagon opposes this effect. Insulin's effect is mediated through phosphorylation of cAMP Response Element Binding Protein. Thyroid hormone acts, after a lag period of about 36 hrs, to markedly increase hepatic HMGR expression as a result of an increased rate of transcription as well as stabilization of the mRNA. Glucocorticoids oppose the mRNA stabilization. Statins act to increase hepatic HMGR protein levels as much as 700-fold through a combination of increased transcription, increased translation and stabilization of HMGR protein. Thyromimetics act to increase HMGR mRNA levels and also hepatic LDL receptor mRNA and protein levels. Oxylanosterols act to profoundly lower hepatic HMGR protein levels by acting to decrease the rate of translation. The physiological and pharmacological factors that modulate hepatic HMGR expression appear to employ a plethora of regulatory strategies. The molecular details of these regulatory mechanisms are the subjects of several current investigations.
Keywords: hepatic 3-hydroxy-3-methylglutaryl